The haustorium: The root of biotrophic fungal pathogens - Mapuranga, Johannes; Zhang, Lirong; Zhang, Na; Yang, Wenxiang (Frontiers in Plant Science, 2022)
Biotrophic plant pathogenic fungi are among the dreadful pathogens that continuously threaten the production of economically important crops. The interaction of biotrophic fungal pathogens with their hosts necessitates the development of unique infection mechanisms and involvement of various virulence-associated components. Biotrophic plant pathogenic fungi have an exceptional lifestyle that supports nutrient acquisition from cells of a living host and are fully dependent on the host for successful completion of their life cycle. The haustorium, a specialized infection structure, is the key organ for biotrophic fungal pathogens. The haustorium is not only essential in the uptake of nutrients without killing the host, but also in the secretion and delivery of effectors into the host cells to manipulate host immune system and defense responses and reprogram the metabolic flow of the host. Although there is a number of unanswered questions in this area yet, results from various studies indicate that the haustorium is the root of biotrophic fungal pathogens. This review provides an overview of current knowledge of the haustorium, its structure, composition, and functions, which includes the most recent haustorial transcriptome studies.